Making the most of mess : reliability and policy in today's management challenges - Roe, Emery (e-Duke books scholarly collection., 2013)
Emery Roe suggests productive ways to manage ""messes""-complex, large-scale problems that cannot be easily resolved. He develops his argument through an analysis of the 2008 financial crisis and policymakers' responses to it.